The prevalence of PTSD symptoms among psychology students and its association with working memory - Sunna Dís Jónasdóttir 1986- (2022)
Post-traumatic stress disorder (PTSD) is a severe psychiatric disorder and can have multiple detrimental consequences. Clinical studies have shown changes in cognitive function such as in verbal learning and memory, speed of processing, and in working memory. The current study examined whether there is a difference in memory and working memory among people with PTSD and others. The study was conducted at Reykjavik University and there were 48 participants that took part, all older than 18 years, psychology students and faculty members. Participants were presented with various tests. Operation Span Test (OSPAN) and DIGIT Span Backwards were used to measure working memory, DIGIT Span Forward was used to measure attention and short –term memory, finally The Post traumatic Stress Disorder Checklist for DSM-5 (PCL-5) was used to evaluated symptoms of traumatic stress disorder. Results showed that 27.1% of participants showed clinical signs of PTSD. The PTSD group scored lower on OSPAN and backwards Digit Span but scored higher on Digit Span forward compared to those who did not have PTSD, Even so there was no difference between PTSD and score on OSPAN and Digit Span tests. Keywords: Post-traumatic stress disorder (PTSD), trauma, working memory, memory. Áfallastreituröskun (PTSD) er alvarleg geðröskun og getur haft margvíslegar skaðlegar afleiðingar. Klínískar rannsóknir hafa sýnt breytingar á vitrænni virkni , svo sem í munnlegu námi og minni, vinnsluhraða og í vinnsluminni. Í þessari rannsókn var kannað hvort munur væri á vitrænni starfsemi hjá fólki með áfallastreituröskun og annarra. Rannsóknin var gerð við Háskólann í Reykjavík og tóku þátt 48 þátttakendur, allir eldri en 18 ára. Úrtakið voru kennarar og sálfræðinemar við Háskólann í Reykjavík. Þátttakendum svöruðu nokkrum hugrænu verkefnum Operation Span Test (OSPAN) og DIGIT Span Backwards voru notuð til að mæla vinnsluminni, DIGIT Span Forward var notað til að mæla athygli og skammtímaminni og að lokum var The Posttraumatic Stress Disorder Checklist fyrir ...